Integration of Solution-Focused Brief Counseling with Creative Arts: A Literature Review - Widiasari, Santi; Ramli, M.; Wahyuni, Fitri (International Journal of Applied Guidance and Counseling, 2024)
In face developments of the era that are changing so quickly, counselor creativity be one of the important indicator that needs to be developed in implementation counseling service. This counselor's creativity can encourage achievement counseling service goals that was meaningful and has a significant impact on changes in counselee behavior. The aim of this article is to describe the opportunities of integration solution-focused brief counseling with the creative arts. This article is study literature with a structured and systematic meta-analysis from ideas development and research of solution-focused brief counseling with the creative arts. This article is an analysis of 46 articles published between 2007 and 2022 . In addition, there are 5 scientific articles directly related to the combination of brief counseling focus solution with creative arts. The results of an analysis of these articles found that integration of solution-focused brief counseling with the creative arts is a counseling innovation by integrating principles in creative counseling that seeks to help students realize their abilities and potential so that they can come up with solutions to the problems they have. Integration of the creative arts in solution-focused brief counseling is important to do to increase the effectiveness of the counseling services provided. Creative art that can support the effectiveness of solution-focused brief counseling are drawings, puppets, metaphors, and sand trays. The findings of this study provide recommendations for further research to identify the effectiveness of solution-focused brief counseling with other creative arts empirically in overcoming certain problems in counselees.